WEAR RESISTANT OF CACO3/FLY-ASH CERAMIC MATRIX COMPOSITE - Hadi, Qomarul; Hardiyanto, Dwiki (Indonesian Journal of Engineering and Science, 2024)
This study aimed to investigate the potential of utilising fly ash, a harmful byproduct of coal waste, in the manufacturing of composite materials to reduce its environmental impact. Calcium carbonate (CaCO3) and fly ash were mixed with zinc stearate using the powder metallurgy method to create wear-resistant samples. The compaction load was adjusted to achieve optimal low-pressure compaction, with pressures of 22.75 MPa, 23.45 MPa, 24.14 MPa, and 24.83 MPa used for single punch pressing. After 10 minutes of holding time, sintering was conducted at 900 OC for 1 hour. The raw materials were tested using X-ray diffraction (XRD) and sieved based on the mesh size. The composite was characterised through various tests, including density testing, wear testing, and scanning electron microscopy (SEM) to observe the microstructure. The density value increased with the compaction load, with a maximum apparent density of 1.794 g/cm3 and the highest porosity percentage at a pressure of 22.75 Mpa of 31.155%. Furthermore, the specific wear value decreased as the compaction load increased, with the lowest specific abrasion value of 1.17 x 10-6 mm2/kg. Therefore, using fly ash to produce composite materials is a promising solution to reduce the negative impact of coal waste while producing wear-resistant materials.